Mucolipin 1 positively regulates TLR7 responses in dendritic cells by facilitating RNA transportation to lysosomes. (19th September 2014) - Li, Xiaobing; Saitoh, Shin-ichiroh; Shibata, Takuma; Tanimura, Natsuko; Fukui, Ryutaro; Miyake, Kensuke
Abstract : Mucolipin 1 controls nucleic acid transport and TLR7/9-mediated inflammation Abstract: Toll-like receptor 7 (TLR7) and TLR9 sense microbial single-stranded RNA (ssRNA) and ssDNA in endolysosomes. Nucleic acid (NA)-sensing in endolysosomes is thought to be important for avoiding TLR7/9 responses to self-derived NAs. Aberrant self-derived NA transportation to endolysosomes predisposes to autoimmune diseases. To restrict NA-sensing in endolysosomes, TLR7/9 trafficking is tightly controlled by a multiple transmembrane protein Unc93B1. In contrast to TLR7/9 trafficking, little is known about a mechanism underlying NA transportation. We here show that Mucolipin 1 (Mcoln1), a member of the transient receptor potential (TRP) cation channel gene family, has an important role in ssRNA trafficking into lysosomes. Mcoln1 −/− dendritic cells (DCs) showed impaired TLR7 responses to ssRNA. A mucolipin agonist specifically enhanced TLR7 responses to ssRNAs. The channel activity of Mcoln1 is activated by a phospholipid phosphatidylinositol (3, 5) bisphosphate (PtdIns(3, 5)P2 ), which is generated by a class III lipid kinase PIKfyve. A PIKfyve inhibitor completely inhibited TLR7 responses to ssRNA in DCs. Confocal analyses showed that ssRNA transportation to lysosomes in DCs was impaired by PIKfyve inhibitor as well as by the lack of Mcoln1. Transportation of TLR9 ligands was also impaired by the PIKfyve inhibitor. These results demonstrate that the PtdIns(3, 5)P2 –Mcoln1 axis has an important role in ssRNA transportation into lysosomes in DCs.